IbM Mix Farming Dengan â€œNutrisi Alamiâ€ Solusi Pemenuhan Kebutuhan Pangan yang Sehat dan Segar - Swasono, M. Aniar Hari; Mamilianti, Wenny (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2017)
The livelihoods the people of Sekarmojo village are mostly farmers and farm laborers. The average level ofeducation is primary school. This becomes an obstacle in technology adoption.  The village location is linked to a stonypath and not yet all paved. This condition causes the community of Sekarmojo Village not yet maximally in adoptinginformation especially information technology. Issues that exist within the partner community group, among others : (1)the lack of knowledge and technology in improving local resource-based welfare, (2) extensive yard has not been usedsustainably, (3) livestock and fishery activities have not been managed with sustainable technology, (4) housewife'sactivities yet leads to productive activities, (5) the supply of food (fish, meat and vegetables) that fresh can not be obtainedat any time. The purpose of this activity are: (1) Providing science and technology to the community in managing yardthat produces vegetables, meat and organic fish, (2) realizing sustainable food home area in Sekarmojo PurwosariPasuruan village, (3) increasing of human resource quality in production activity agriculture, (4) creating new businessopportunities within the community, (5) opening and expanding networks of cooperation with private and governmentagencies. The benefits of this activity are (1) the fulfillment of family food needs (2) the community has productiveactivities, (3) the formation of new business. Methods of implementation include community counseling, training, directdemonstration / practice, mentoring and evaluation to see the effectiveness of the program so that the program will besocialized efficiently. The results have been achieved, among others: (1) Partners have been able to create naturalnutrients that are useful for planting vegetables, fish farming and chicken farming. (2) Partners have an understandingand an increasing insight in the management of the yard. (3) Partners have new businesses that can supplementhousehold income, namely vegetable seeding business and organic vegetable sales. (4) Partners have started to make thedesign / business plan of breeding business